E-Water Level: Educational Kit For Testing Student Knowledge On Transient Response Using Water Level Control - Azmi, Ezzatul Farhain; Ishak, Muhammad Firdaus; Samsudin, Adam; Zainal Abidin, Amar Faiz; Kadiran, Kamaru Adzha (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Control Principle course is a part of syllabus in the diploma or degree in Electrical Engineering programme where students are exposed to topics such as time response analysis. One of the topics in this course is Transient Response analysis where it requires students to calculate the characteristic of the response based on set of formula. One of the difficulty encounters in delivering this topic is students having difficulty to relate the theory with the application as most theoretical part of this topic does not explain on how the transient response graph is obtained in the first place. In order to address this problem, this paper proposed E-Water Level educational kit that can be used by student in order to understand independently the transient response analysis by applying theory on the water level control application where the student knowledge on Transient Response parameters are tested, namely the delay time, rise time, damping ratio and setting time. The system consists of Arduino Microcontroller, water tank, water pump, relay, ultrasonic sensor and electronic display. The novelty of this educational kit is that the educational kit is adaptive in bridging the gap between theory and application in which the data is generated by real application of water level and the answers for the questions are automatically generated based on the data obtained. Thus, each student will experience different set of question.